2022
DOI: 10.1093/plphys/kiac063
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group A3 enhances transcription of the DNA demethylase gene SlDML2 to promote tomato fruit ripening

Abstract: DNA methylation plays an important role in regulating tomato (Solanum lycopersicum) fruit ripening. Although SlDML2, a DNA demethylase (DML) gene, is critically involved in tomato fruit ripening, little is known about genes that regulate its expression. Using yeast one-hybrid screening, we identified a High Mobility Group A protein, named SlHMGA3, and demonstrated its binding activity to the AT-rich region of the SlDML2 promoter. We produced slhmga3 tomato mutants using CRISPR/Cas9 and observed that slhmga3 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Delays in the fruit ripening of the SlALKBH2 mutant may be a result of the feedback regulation of SlDML2 stability [ 148 ]. Recent studies have shown that SlHMGA3 encoding High-Mobility Group (HMG) A proteins can bind to the SlDML2 promoter and activate its expression, resulting in the promoter DNA methylation of ripening-related TFs regulating ETH biosynthesis and signal transduction [ 149 ].…”
Section: Epigenetic Modifications Of Fruit Softeningmentioning
confidence: 99%
“…Delays in the fruit ripening of the SlALKBH2 mutant may be a result of the feedback regulation of SlDML2 stability [ 148 ]. Recent studies have shown that SlHMGA3 encoding High-Mobility Group (HMG) A proteins can bind to the SlDML2 promoter and activate its expression, resulting in the promoter DNA methylation of ripening-related TFs regulating ETH biosynthesis and signal transduction [ 149 ].…”
Section: Epigenetic Modifications Of Fruit Softeningmentioning
confidence: 99%
“… Ma et al (2019) identified a putative negative regulator of cotton plant height near one of the two QTL (HATH13.1) that co-localized with the plant height QTL from Ma et al (2019) . Near the second QTL detected in our study in the co-localized region, we identified an AT hook DNA binding motif like gene, reported to enhance plant height upon overexpression in Zoysia japonica ( Jeong et al, 2020 ) and reduced plant height in a CRISPR/Cas9 mutant of sihmg3 (protein that contains 4 AT hook repeats) in tomato ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 73%
“…In DML2 loss-of-function mutants generated by targeted editing, increased DNA methylation was found not only in genes induced during ripening but also in genes repressed during ripening [99]. However, a recent study found that the highly mobile protein positively regulates DML2 expression of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGA) [100]. In [101], the expression of the mammalian demethylase TET3c (ten-eleven translocation) in tomatoes resulted in the activation of expression of the previously undescribed gene CEN1.1.…”
Section: Epigenetic Modifications As Regulators Of Ripeningmentioning
confidence: 99%